Advising the Command Best Practices from the Special Operations Advisory Experience in Afghanistan - Helmus, Todd C. (RAND Corporation, 2015)
Special Operators assigned to Special Operations Advisory Groups advise the commanders and staff of the Afghan Special Security Forces. Drawing on in-depth interviews with these personnel, this report identifies best practices for operational level advising. Topics addressed include rapport building, the advising engagement, integration, sustainability, pre-deployment training, and continuity of operations.